Open-ended bond funds: Systemic risks and policy implications - Stijn Claessens; Ulf Lewrick (Aussenwirtschaft, 2022)
Alongside other non-bank financial intermediaries, open-ended funds that invest in bonds ("bond OEFs") have grown rapidly over the past two decades. Besides their size, their business model and role in recent events suggest that bond OEFs can amplify stress in financial markets. The March 2020 market turmoil tested the effectiveness of bond OEFs' tools in dealing with large investor redemptions in the presence of liquidity mismatches. Their tools notwithstanding, bond OEFs had to liquidate assets on an elevated scale, thus collectively adding to bond market pressures. Without central bank interventions, broader fire sale dynamics could have been triggered. Regulation that takes a macroprudential perspective of the sector could support financial stability by ensuring that tools internalize the effect of spillovers arising from bond OEFs' actions.
Keywords: G01; G23; G28; C72; 330; liquidity; regulation; financial stability